A Case Study on Aggressive Behavior in Early Childhood Children with Left-Brain Dominance - Rahmah Rohadatul ‘Aisy; Brigita Puridawaty; Vina Vebianti; Ai Nela; Dian Mardiana; Nia Soniati (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Aggressive behavior in early childhood is a multidimensional phenomenon influenced by the interaction between neurobiological and environmental factors. This study aims to analyze aggressive behavior in early childhood with left-hemisphere dominance and to examine its relationship with social learning processes and emotional regulation. A qualitative approach with an instrumental case study design was employed. The subject was a boy aged five years and eleven months identified as having left-brain dominance and a high level of aggressiveness based on psychological assessment results. Data were collected through participatory observation, in-depth interviews with parents and a child psychologist, and analysis of psychological documents. Thematic analysis was conducted based on Bandura’s social learning theory, Pavlov’s classical conditioning theory, and executive function concepts. The findings indicate that aggressive behavior manifested in physical and verbal forms, triggered by frustration, cognitive rigidity, and limited emotional regulation. Left-brain dominance functioned as an indirect risk factor when not balanced by social-emotional maturity. This study emphasizes the importance of holistic interventions involving family and school to support optimal social-emotional development in early childhood.